Clinical utility of daylight photodynamic therapy in the treatment of actinic keratosis – a review of the literature - Nguyen M; Sandhu SS; Sivamani RK (Dove Medical Press, 2019)
Mimi Nguyen,1 Simran S Sandhu,1 Raja K Sivamani1–41Department of Dermatology, University of California – Davis, Sacramento, CA, USA; 2Department of Biological Sciences, California State University Sacramento, Sacramento, CA, USA; 3College of Medicine, California Northstate University, Elk Grove, CA, USA; 4Department of Dermatology, Pacific Skin Institute, Sacramento, CA, USAAbstract: Actinic keratosis (AK) is an early in situ squamous cell carcinoma that results from UV light exposure and has the potential to evolve into invasive tumor. Therefore, it is crucial that AKs are monitored and treated appropriately. Photodynamic therapy (PDT) is a treatment option that is minimally invasive and leaves patients with cosmetically superior results. However, disadvantages of PDT include pain and lengthy clinic visits. Accordingly, there has been much interest in the use of daylight photodynamic therapy (daylight-PDT) as a more convenient and less painful alternative to conventional photodynamic therapy (c-PDT). Current evidence shows that daylight-PDT is noninferior to c-PDT in the short and long term. Patients reported decreased pain with daylight-PDT and were more satisfied with the procedure (P<0.001). Current evidence suggests that 2 hrs of daylight exposure was sufficient for treatment, and its efficacy does not appear to be limited by weather conditions. Given the decreased intensity of treatment, daylight-PDT is better for mild disease, as it is less effective in moderate-to-thick AKs. Though further studies are still needed to refine the technique, daylight-PDT is a potential alternative to c-PDT for thin-to-moderate AKs and should be offered to patients with lower pain tolerance or busy schedules.Keywords: daylight, conventional, photodynamic therapy, actinic keratosis, pretreatment